Migration Paths for Smart Grids and Their Evaluation Using a Case Study - Flore, Agnetha; Clausen, Marie; Uslar, Mathias (Frontiers in Energy Research, 2019)
This contribution will deal with the topic of migration paths in the Smart Grid domain. Migration paths - defined as development steps from one development stage to the next - will be investigated to support network operators in planning the processes and technologies necessary to meet the future requirements of the energy system transformation. For this purpose, a process model was developed which is presented and applied on the basis of a case study. The dependencies and influences between the dimensions considered are investigated and an algorithm is developed and used for their qualitative evaluation. By analyzing and evaluating the migration paths, particularly critical development steps on the entire roadmap that require special control can be shown to the distribution grid.